2000
DOI: 10.1046/j.1523-1739.2000.99276.x
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Prioritizing Domestic Animal Breeds for Conservation Purposes at the National Level: a Norwegian Case Study

Abstract: Although encompassing only a handful of species, domestic animals have had profound effects on food production for humankind and on human societies. On a global basis, a large proportion of breeds are currently in danger of becoming extinct in the near future. At this critical time, resources are limited and only a selected number of breeds may be supported by concrete conservation programs. I present a framework to facilitate decision making on a national level as to which breeds to support for conservation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 9 publications
1
65
0
6
Order By: Relevance
“…The primary objective of livestock conservation for developing countries is conservation for sustainable use [22,25]. Conservation is not only about endangered breeds but also about those that are not being utilized efficiently [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary objective of livestock conservation for developing countries is conservation for sustainable use [22,25]. Conservation is not only about endangered breeds but also about those that are not being utilized efficiently [1].…”
Section: Introductionmentioning
confidence: 99%
“…However, the human socio-political context needs to be fully understood for conservation priorities to have any impact on human livelihoods [19]. Ruane [22] proposed a framework that incorporates both genetic diversity and non-genetic criteria for prioritizing breeds at the national level. However, applications of this framework are lacking and conservation priorities have largely been based solely on contributions of breeds to genetic diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are several criteria to prioritize breeds for conservation programs (Bennewitz and Meuwissen, 2005), the endangerment status of breeds is the most important criterion (Ruane, 2000), which can be expressed in terms of the effective population size. The N e of GSA and GUS population was reported to be higher (165 and 65, respectively) in the past (Weigel, 2001;Maiwashe et al, 2006) than the results observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This is indeed reflected in the diversity observed for both markers. Marker diversity, even though properly evaluated, needs to be completed by more detailed breed characterisation, as pointed out by several authors (Ruane 2000;Barker 2001;Alderson 2003). This implies setting a balance between genetic diversity and genetic merit, as the latter may be ''perceived'' (Chaiwong and Kinghorn 1999;Piyasatian and Kinghorn 2003), or, more generally, between distinctiveness and utility (Weitzman 1998).…”
Section: Discussionmentioning
confidence: 99%